STUDYING OF THE AMINO ACID AND FLAVONOID COMPOSITION OF R. REFRACTA AND R. HYBRIDA PLANTS (Scientific journal of the Fergana State University, 2025)
In this article, presents the results of studying the amino acid and flavonoid composition of R.hybrida and R.refracta plants growing in the Fergana region. All protein-forming amino acids were found in the aboveground part of the R. refracta plant. The cysteine was found in the greatest amount, its amount was 42.39% of the total amino acids. All essential amino acids were determined in the plant, the amount of which was 24.81% of the total amino acids. Apigenin, rutin and gallic acid were found in the aboveground part of the R.refracta plant, apigenin, rutin, hyperazide and gallic acid were found in the seeds, and apigenin, rutin, hyperazide and gallic acid were found in the aboveground part of R.hybrida. Apigenin and rutin predominate in the aboveground part of the R. refracta plant, hyperazide in the seeds of the R.refracta plant, and gallic acid in the aboveground part of the R.hybrida plant. Flavonoids of the R.hybrida plant predominate in quantitative and qualitative composition. The R.hybrida and R.refracta plants can be recommended for the production of pharmaceutical, cosmetic and food mixtures.